Investigation of the female athlete triad in Japanese elite wheelchair basketball players - Shimizu, Y.; Mutsuzaki, H.; Tachibana, K.; Hotta, K.; Wadano, Y. (Medicina, 2020)
Background and objectives: Para-sports have become increasingly competitive, necessitating greater physical activity; secondary disorder prevention is therefore crucial. Among secondary disorders, the female athlete triad (FAT) is defined as low energy availability (EA), menstrual dysfunction, and low bone mineral density (BMD); although studied in able-bodied athletes, reports on female para-athletes are scarce. We retrospectively investigated the FAT in wheelchair basketball players in the Japanese national team. Materials and Methods: Thirteen female wheelchair basketball players (mean age: 28.9 ± 8.1 years) were enrolled. The medical history (underlying diseases, gynecological disorders, and stress fractures), athletic and sport-specific parameters (wheelchair basketball classification, and wheelchair usage conditions), hematological status (hemoglobin, iron, estradiol, progesterone, total P1NP, and TRACP-5b levels), nutritional status (total energy, protein, calcium, and iron intake), body composition (BMD and lean body mass (LBM)), and EA were assessed. Results: Two (15.4%) had pertinent gynecological histories and six (46.2%) had menstrual cycle disorders. Three (23.1%) experienced excessive menstrual flow and nine (69.2%) had menstrual pain. No stress fractures were reported. All laboratory data were within normal limits. Total energy and iron intakes based on age-specific requirements were 99.8% and 59.8%, respectively. Iron and hemoglobin levels correlated with menstrual flow (? = -0.63, p = 0.019 and ? = -0.56, p = 0.046, respectively). The mean total BMD was 109.2%, and the mean EA (41.4 kcal/kg LBM) was lower than recommended levels. The leg BMD in spinal disorders was significantly lower than that in skeletal disorders (p = 0.003). The arm LBM was higher (150.6%) than that of age-matched controls. Conclusion: Among female wheelchair basketball players with FAT, the total BMD was comparable to that of age-matched controls; however, leg BMD in spinal disorders was significantly lower than that in skeletal disorders. Players with heavy menstrual flow had lower hemoglobin and iron levels. Further research is needed on the FAT to optimize health and sports performance among para-athletes